EVALUATING LEARNING OUTCOMES STRATEGIES FOR ENHANCING TEACHING EFFECTIVENESS IN THE CLASSROOM - Ni Putu Ika Putri Sujianti; Ida Bagus Made Sanjiyasa; Jetlia Mesa; Matius Saingo; Perinus Bili (CV. Tirta Pustaka Press, 2025)
This study aims to explore the relationship between learning outcome evaluation strategies and teaching effectiveness in the classroom. In the context of modern education, which emphasizes active and competency-based learning, evaluation is no longer viewed merely as a final measurement tool but as an integral part of the learning process that supports pedagogical decision-making. This research employed a mixed-methods approach, combining quantitative data from student assessments with qualitative data from interviews, classroom observations, and document analysis. The findings indicate that consistent implementation of formative assessments enhances teachers’ ability to respond adaptively to students’ needs. Moreover, authentic assessment strategies—such as portfolios, project-based evaluations, and self-reflections—are proven to strengthen student engagement and support more holistic learning achievements. Student involvement in the evaluation process, through self-assessment and peer-assessment, also contributes positively to their learning awareness and personal responsibility. These findings underscore that well-designed evaluation practices can serve as a strategic foundation for more effective, meaningful, and student-centered instruction. The study recommends strengthening teacher capacity in designing and applying assessments, along with institutional support to foster a reflective and collaborative evaluation culture within schools.